Editorial: Peruvian Reality - Analysis and Criticism - El Director (2010)
The articles published on this occasion have an evident analytical and critical vocation with respect to the Peruvian reality, without neglecting academic rigor. Therefore, we invite the reader to take these proposals with the intention of discussing, accurately describing, diagnosing and proposing alternatives. The topics presented in this issue of IECOS magazine want to clarify the process of economic growth and development, proposing to address its shortcomings. Whether due to the absence of a territorial development policy, obstacles to decent work, or the difficulties inherent in the analysis of power transmission, our authors always want to face these limits and propose alternatives.